1992
DOI: 10.11150/kansenshogakuzasshi1970.66.1615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of UTI in Hospitalized Elderly Patients, with Particular Reference to the Use of Diapers

Abstract: We investigated the clinical and laboratory data of 215 hospitalized patients (mean age were 76.9 +/- 12.1) to analyze both the characteristics of senile UTI and the influence of the way of urination. UTI was present in 121 of 1897 patients (6.4%), 95 of whom (78.5%) were female. Comparison of the parameters between non-infected and infected patients were as follows: body temperature was 36.57 +/- 0.64 degrees C vs. 37.49 +/- 0.77 degree C; WBC, 5410 +/- 2040/microliters vs. 7260 +/- 3230/microliters; CRP, 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The diagnostic criterion for pyuria in this document was > 5 leukocytes/hpf, whereas in other guidelines the value of above 10 leukocytes/hpf was suggested [ 6 ]. The study confirmed also other author’s findings that Escherichia coli remained the major micro-organism responsible for UTIs in hospitalized older people—it was cultured in 73.3% of cases [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…The diagnostic criterion for pyuria in this document was > 5 leukocytes/hpf, whereas in other guidelines the value of above 10 leukocytes/hpf was suggested [ 6 ]. The study confirmed also other author’s findings that Escherichia coli remained the major micro-organism responsible for UTIs in hospitalized older people—it was cultured in 73.3% of cases [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…In Japan, disposable diapers are commonly used in nursing homes as they are effective for bedridden elderly patients. Skin contamination by excrement causes skin irritation, decubitus ulcer, and urinary tract infection [4,5]. Ideally, dia-pers should be changed immediately after urination.…”
Section: Introductionmentioning
confidence: 99%